Neuraminidase and SIGLEC15 modulate the host defense against pulmonary aspergillosis - Intan M.W. Dewi (Cell Reports Medicine, 2021)
Summary: Influenza-associated pulmonary aspergillosis (IAPA) has been reported increasingly since the advent of use of neuraminidase (NA) inhibitors following the 2009 influenza pandemic. We hypothesize that blocking host NA modulates the immune response against Aspergillus fumigatus. We demonstrate that NA influences the host response against A. fumigatus in vitro and that oseltamivir increases the susceptibility of mice to pulmonary aspergillosis. Oseltamivir impairs the mouse splenocyte and human peripheral blood mononuclear cell (PBMC) killing capacity of A. fumigatus, and adding NA restores this defect in PBMCs. Furthermore, the sialic acid-binding receptor SIGLEC15 is upregulated in PBMCs stimulated with A. fumigatus. Silencing of SIGLEC15 decrease PBMC killing of A. fumigatus. We provide evidence that host NA activity and sialic acid recognition are important for anti-Aspergillus defense. NA inhibitors might predispose individuals with severe influenza to invasive aspergillosis. These data shed light on the pathogenesis of invasive fungal infections and may identify potential therapeutic targets.